β-Cyclodextrin-Based Inclusion Complexation Bridged Biodegradable Self-Assembly Macromolecular Micelle for the Delivery of Paclitaxel - Chen, Yanzuo (PLoS One, 2016)
In this study, a novel adamantanamine-paclitaxel (AD-PTX) incorporated oligochitosan- carboxymethyl-β-cyclodextrin (CSO-g-CM-β-CD) self-assembly macromolecular (CSO-g-CM-β-CD@AD-PTX) micelle was successfully prepared in water through sonication. The formed molecules were characterized by Fourier transform infrared spectroscopy, proton nuclear magnetic resonance (NMR) spectroscopy, two-dimensional NMR, elemental analysis, and liquid chromatography-mass spectrometry, while the correspondent micelles were characterized by dynamic light scattering and transmission electron microscopy. We showed that the macromolecular micelle contained a spherical core-shell structure with a diameter of 197.1 ± 3.3 nm and zeta potential of −19.1 ± 4.3 mV. The CSO-g-CM-β-CD@AD-PTX micelle exhibited a high drug-loading efficacy up to 31.3%, as well as a critical micelle concentration of 3.4 × 10(-7) M, which indicated good stability. Additionally, the in vitro release profile of the CSO-g-CM-β-CD@AD-PTX micelle demonstrated a long-term release pattern, 63.1% of AD-PTX was released from the micelle during a 30-day period. Moreover, the CSO-g-CM-β-CD@AD-PTX micelle displayed cytotoxicity at a sub-μM scale similar to PTX in U87 MG cells, and CSO-g-CM-β-CD exhibited a good safety profile by not manifesting significant toxicity at concentrations up to 100 μM. These results indicated that β-CD-based inclusion complexation resulting in biodegradable self-assembled macromolecular micelles can be utilized as nanocarrier, and may provide a promising platform for drug delivery in the future medical applications.